THE IMPACT OF TRANSLATION STUDIES ON LANGUAGE LEARNING AND TEACHING (Modern education and development, 2024)
This article explores the ways in which Translation Studies, a discipline traditionally focused on the analysis and practice of translation, can positively influence language learning and teaching. It examines how translation techniques and theories can enhance learners' linguistic competence, cultural awareness, and critical thinking skills. Additionally, it discusses how translation can be integrated into language classrooms to create engaging and meaningful learning experiences. By drawing on research and practical examples, this article demonstrates the potential of Translation Studies to enrich language education at all levels.